Implementation and Evaluation of a Complex Pumped-Storage Hydropower Plant with Four Units, Common Penstock, and Surge Tank in a Real-Time Digital Simulator - Hasan Akbari; Juan I. Pérez-Díaz; José-Ignacio Sarasúa; Robert Schürhuber (Energies, 2023)
The demand for energy storage systems is rising together with the proportion of renewable energy sources (RES) in power systems. The highest capacity among the various energy storage systems in power systems is provided by pumped-storage hydropower (PSH). In this paper, the ability of the real-time digital simulator (RTDS), e.g., dSpace–SCALEXIO, to emulate a complex pumped-storage hydropower plant with four units, two common penstocks, a surge tank, and a long headrace tunnel is investigated. The RTDS is the smart brain of an advanced lab setup called power hardware in the loop (PHIL), which is an extremely safe and useful lab system for electrical power system research and testing hardware and methods under various conditions. In this research, the capability of an RTDS to emulate the behavior of a pumped-storage hydropower plant including four Francis pump-turbines, four short penstocks, two common penstocks, a surge tank, and a long headrace tunnel is evaluated. Francis pump-turbines are modelled based on the hill chart-based interpolation and waterways including penstocks and headrace tunnel are modelled based on the polynomial approximation of a hyperbolic function. Finally, the results from the RTDS are presented and discussed. According to the results of the paper, we confirm that the RTDS can accurately emulate the hydraulic, mechanical, and electrical transients of a pumped-storage hydropower plant with a complex configuration.